Description of the Third Instar Larvae of Terellia tussilaginis and T. gynaecochroma (Diptera, Tephritidae) - Troshyn, A. M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The third instar larvae of Terellia (Cerajocera) tussilaginis (Fabricius, 1775) and T. (C.) gynaecochroma (Hering, 1937) are described and figured for the first time based on material from Kryvyi Rih vicinities (Ukraine).